The Role of Social Media Influencer Attractiveness and Credibility in Increasing Consumer Engagement and Purchasing Decisions: An Empirical Study on Skincare Products - Marli, Marli; Dwi Danesty Deccasari (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the role of social media influencers in increasing consumer engagement and purchasing decisions for skincare products. The analysis results show that consumer engagement has a significant effect on purchasing decisions (coefficient = 0.426, p = 0.001), confirming consumer engagement as a key factor in purchasing behavior. The influencer credibility variable has the strongest influence on consumer engagement (coefficient = 0.537, p < 0.001) and purchasing decisions (coefficient = 0.254, p = 0.020), while influencer attractiveness has a positive but weaker and marginal influence on engagement (coefficient = 0.195, p = 0.060) and contributes directly to purchasing decisions. Effect size analysis (f-square) confirms the dominance of credibility as the main factor in forming engagement and purchasing decisions. In addition, consumer engagement significantly mediates the influence of attractiveness and credibility on purchasing decisions, with a more dominant mediating role coming from credibility. These findings provide a theoretical contribution by confirming the mediating mechanism of engagement in the relationship between influencer attributes and purchasing decisions, while providing practical implications for digital marketing strategies for skincare products.